2015
DOI: 10.1111/pan.12614
|View full text |Cite
|
Sign up to set email alerts
|

An update on newer pediatric supraglottic airways with recommendations for clinical use

Abstract: Supraglottic airways are an established part of routine and emergency pediatric airway management, including use in difficult airways and neonatal resuscitation. With the introduction of newer supraglottic airways in children, efficacy can only be determined by comparing these devices with those that are already well established (laryngeal mask airway Classic and laryngeal mask airway ProSeal). This narrative review aims to present the current literature on these newer supraglottic airways and give recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 92 publications
6
52
0
3
Order By: Relevance
“…The initial airway leak pressures in this study for the AuraGain are similar to previous studies with the LMA Supreme [1,5,6,12], but slightly lower than the reported airway leak pressures of the LMA ProSeal [2,13] and i-gel [14][15][16] in children. The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The initial airway leak pressures in this study for the AuraGain are similar to previous studies with the LMA Supreme [1,5,6,12], but slightly lower than the reported airway leak pressures of the LMA ProSeal [2,13] and i-gel [14][15][16] in children. The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance.…”
Section: Discussionsupporting
confidence: 77%
“…The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance. The 10-min airway leak pressures are similar to the airway leak pressures demonstrated in recent reports on the LMA ProSeal [2,17,18] and igel [1,15,16] in children.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Second-generation supraglottic devices may have the added benefi ts of allowing drainage of gastric contents and facilitation of endotracheal intubation in these situations. (42) Recommendation When ventilation is diffi cult and/or endotracheal intubation is not possible during paediatric resuscitation, appropriate supraglottic airway devices, especially laryngeal mask airways, if available, are recommended when used by experienced providers to provide a patent airway and support ventilation.…”
Section: Laryngeal Mask Airway and Supraglottic Devicesmentioning
confidence: 99%